Postopek modeliranja v okviru množičnega vrednotenja nepremičnin - Ulbl, Melita (Geodetski vestnik, 2022)
The mass valuation of real estate in Slovenia is based on valuation models, which are made based on realised real estate market data and illustrate the functioning of the real estate market. The system is based on valuation models that simulate the behaviour of the real estate market and allow a statistically reliable assessment of market value. Models are formed using statistical methods of processing real estate market data. This paper presents the quality verification process and preparation of real estate market data. These data are used to design evaluation models or modelling, which consists of time adjustment of prices or rents, zoning, levelling, calibration, and analysis of quality parameters. Finally, the critical information of the modelling process made in the context of real estate mass valuation in Slovenia is summarised.
Keywords: množično vrednotenje nepremičnin; modeliranje; umerjanje